Acute Portomesenteric Venous Thrombosis following Laparoscopic Small Bowel Resection and Ventral Hernia Repair - Bhradeev Sivasambu; Meera Yogarajah; Thomas Wilson (Case Reports in Gastrointestinal Medicine)
Acute portomesenteric venous thrombosis is a rare but life-threatening complication of laparoscopic surgery that has been described in literature. Prompt diagnosis and early initiation of treatment are vital to prevent life-threatening complications such as mesenteric ischemia and infarction. A 51-year-old lady had laparoscopic small bowel resection and primary anastomosis with ventral hernia repair 4 weeks earlier for partial small bowel obstruction. Her postoperative period was uneventful and she was discharged home. Four weeks after surgery she developed watery diarrhea and generalized abdominal pain for four-day duration. A computed tomography of the abdomen revealed portomesenteric venous thrombosis although a computed tomography of abdomen before surgery 4 weeks back did not show any portomesenteric venous thrombosis. We are reporting a case of acute portomesenteric venous thrombosis as a complication of laparoscopic surgery.